Two-dimensional organic framework material, synthetic method thereof and application of two-dimensional organic framework material to battery

By developing two-dimensional organic frame materials to prepare integrated composite separators with comprehensive functions, the problems of zinc dendrites growth and side reactions in zinc ion batteries are solved, effective inhibition of I3- is achieved, and the performance of zinc iodine batteries is improved and Service life.

CN119176920AActive Publication Date: 2024-12-24HAINAN UNIV

Patent Information

Application Number
CN202411362138.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-24
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In large-scale applications, zinc ion batteries face the problems of corrosion and rapid consumption of electrolytes caused by zinc dendrites and zinc metals in aqueous electrolytes. The existing separator materials are costly and have insufficient performance, so they cannot effectively prevent I3- Shuttle through, affects battery performance and service life.

Method used

Develop a two-dimensional organic framework material through 1,3,5 tris(p-formylphenyl)benzene, tris(4-formylphenyl)amine or triazine ring with ethylenedialyhydrazide amide or ethylenedialyl diazine ring The amine reaction forms a covalent organic frame material, designed with suitable pore sizes to allow Zn2+ to pass and limit I3- shuttle through electrostatic interactions, for the preparation of integrated composite membranes with integrated functions.

Benefits of technology

The discharge capacity and cycle life of zinc-iodine batteries have been improved, the problems of zinc dendrites have been overcome, and the side reactions of zinc dendrites have been effectively suppressed, and the battery performance and service life have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176920A_ABST
    Figure CN119176920A_ABST
Patent Text Reader

Abstract

The invention provides a two-dimensional organic framework material, a synthesis method thereof and application of the two-dimensional organic framework material to a battery. The two-dimensional organic framework material is prepared from a monomer A and a ligand B. Wherein the monomer A comprises one of 1, 3, 5 tri (p-formyl phenyl) benzene, tri (4-formyl phenyl) amine, tetraaminophenylmethane or triazine ring. And the ligand B comprises one of oxalyl hydrazine amide and oxalyl diamine. The two-dimensional organic framework material prepared by the method has the aperture of 1.8 nm, and a diaphragm prepared from the two-dimensional organic framework material prepared by the method not only has the capability of efficiently blocking I3 <->, but also has high Zn < 2 + > transmittance, so that normal operation and efficient energy transmission of a battery are maintained. According to the battery prepared by adopting the diaphragm, the overall performance of the zinc-iodine battery can be remarkably improved, including increasing the discharge capacity, improving the cycling stability, improving the total battery performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials, and in particular to a two-dimensional organic framework material, a synthesis method thereof, and application thereof to batteries. Background Art

[0002] The serious safety problems such as battery short circuit, combustion and explosion have hindered its marketization process. In this context, high-safety zinc-ion batteries with water-soluble salts as electrolytes and metal zinc or zinc alloys as negative electrodes have attracted great attention from the industry due to their high reserves, high energy density, low cost and ability to charge and discharge at high currents, becoming a new focus in the battery field. Despite this, the large-scale practical application of zinc-ion batteries still faces some problems that need to be solved. The growth of zinc dendrites and the serious side reactions caused by zinc metal in aqueous electrolytes lead to corrosion and passivation of the zinc negative electrode and rapid consumption of the electrolyte, thereby greatly reducing battery performance and service life, which also affects the prospects for its large-scale application. Existing strategies to improve the reversibility of zinc negative electrodes, such as using "salt-in-water" or organic electrolytes, designing new current collectors, and constructing artificial interface layers, can stabilize the zinc negative electrode to a certain extent and improve battery life, but these methods are costly or may cause environmental pollution, which does not meet the requirements of green and low-cost development of zinc batteries. In addition, the commercial glass fiber separator currently used in zinc batteries is not only expensive, but also has low strength and is easy to break, and has a particularly limited effect on inhibiting zinc dendrites.

[0003] The potential of iodine batteries goes far beyond this. In addition to the conversion between negatively charged ions and single substances, positively charged ions with high reaction potentials are obviously more attractive. For example, in the zinc-iodine battery system, when paired with zinc metal, the theoretical discharge voltage of the entire battery can reach about 1.7V, which can exceed the vast majority of reported mature electrode materials, such as vanadium oxides, manganese oxides and organic polymers. More importantly, multivalent state transformations will bring about the transfer of multiple electrons and thus bring about a huge increase in capacity and energy density. At present, the polyethylene and polypropylene diaphragms widely used in lithium-ion batteries cannot be directly applied to zinc battery systems. In the continuous development of zinc-ion batteries, the commonly used glass fiber diaphragms have shown certain performance. However, in zinc-iodine batteries, the pore size of the glass fiber diaphragm is large, and it is difficult to effectively prevent I3 - The shuttling of the human body affects its effect.

[0004] In modern battery material research, it is particularly important to develop an integrated composite separator with comprehensive functions. This new composite separator not only needs to have high efficiency in blocking I3 - ability, thereby effectively preventing its negative impact on battery performance, while also ensuring that high Zn 2+The transmittance of the membrane should be controlled to maintain the normal operation of the battery and efficient energy transmission. Therefore, the development of diaphragm materials that meet these performance requirements is of great significance to the improvement of the overall performance of the battery. For zinc-iodine batteries, how to effectively improve their discharge capacity, coulombic efficiency and rate performance is one of the main challenges faced in the current research field. In order to solve this problem, researchers need to continuously innovate in diaphragm design and optimization, and find solutions that can take into account multiple performance requirements. This is not only an important direction for theoretical research, but also a bottleneck that needs to be broken through in practical applications. Summary of the invention

[0005] In view of this, the present invention proposes a two-dimensional organic framework material, a synthesis method thereof, and an application thereof to batteries.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The structure of a two-dimensional organic framework material is as follows (1):

[0008]

[0009] Preferably, the synthesis method comprises the following steps:

[0010] Mixing monomer A and ligand B, adding an organic solvent for ultrasonic dispersion, adding a catalyst after dispersion, freezing in liquid nitrogen for 5-10 minutes, sealing after freezing, and heating at 80-150° C. for reaction for 60-90 hours to obtain a mixed solution;

[0011] The mixed solution is washed and dried at 110-130°C to obtain a finished product;

[0012] The monomer A includes one of 1,3,5-tri(p-formylphenyl)benzene, tri(4-formylphenyl)amine, tetraaminophenylmethane or triazine ring;

[0013] The ligand B includes oxalylhydrazide amide or oxalyldiamide.

[0014] Preferably, the mass ratio of the monomer A to the ligand B is 1-2:1.

[0015] Preferably, the organic solvent comprises o-dichlorobenzene and n-butanol in a mass ratio of 0.5-1:1, and the volume mass ratio of the organic solvent to the ligand B is 1 mL: 10-20 mg;

[0016] The catalyst is an acetic acid solution, the volume ratio of the catalyst to the organic solvent is 1:5-7, and the concentration of the acetic acid solution is 6-12M.

[0017] Preferably, the two-dimensional organic framework material is used in the preparation of zinc-iodine battery separators.

[0018] Preferably, the method comprises the following steps:

[0019] (1) dispersing the two-dimensional organic framework material according to claim 1 in an anhydrous ethanol solution, adding a binder A, and obtaining a mixed slurry A;

[0020] (2) dispersing the conductive material in anhydrous ethanol and adding a binder B to obtain a mixed slurry B;

[0021] (3) sequentially filtering the mixed slurry A and the mixed slurry B on the base film, and drying them to obtain a zinc-iodine battery separator;

[0022] Preferably, in step (1), the mass percentage of the binder in the binder is 1-10%;

[0023] The mass ratio of the two-dimensional organic framework material to the binder A is 1-7:1, and the mass ratio of the conductive material to the binder B is 8-10:1;

[0024] The conductive material is one of ketjen black, graphene and graphyne.

[0025] Preferably, in step (1), the binder A and the binder B are one or more of waterborne polyurethane, polyvinylidene ether carbonate, and polyvinylidene fluoride;

[0026] The polymer molecular weight of the polyvinylidene fluoride is 1-100,000. When the polyvinylidene fluoride is used as a binder, N-methylpyrrolidone is used to prepare a polyvinylidene fluoride solution with a mass concentration of 5% to 10%.

[0027] Preferably, the zinc-iodine battery separator prepared by the preparation method.

[0028] Preferably, the zinc-iodine battery separator is used in the preparation of zinc-iodine batteries.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention uses 1,3,5-tri(p-formylphenyl)benzene, tri(4-formylphenyl)amine, tetraaminophenylmethane or triazine ring as monomers, oxalylhydrazideamide or oxalyldiamide as ligands, and the monomers and ligands react to form a covalent organic framework material, which has a suitable pore size design (1.8nm), which allows Zn 2+ Rapid passage and effective restriction of I3 through aperture confinement and electrostatic interaction - Shuttle effect. The present invention develops an integrated composite diaphragm with comprehensive functions.

[0031] The present invention develops an integrated composite diaphragm with comprehensive functions, which is applied to the zinc-iodine battery system. When paired with zinc metal, the theoretical discharge voltage of the whole battery can reach about 1.7V, which can exceed the vast majority of reported mature electrode materials. At the same time, it overcomes the growth of zinc dendrites and the serious side reactions caused by zinc metal in aqueous electrolytes, which lead to corrosion and passivation of the zinc negative electrode and rapid consumption of the electrolyte, thereby greatly reducing the problems of battery performance and service life. Therefore, the diaphragm can greatly improve the battery discharge capacity and cycle life, and contributes an important force to the development of zinc batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a reaction mechanism diagram and a physical diagram of the covalent organic material prepared by using 1,3,5-tri(p-formylphenyl)benzene and oxalylhydrazide amide in Example 1 of the present invention.

[0033] Figure 2 These are the conventional characterizations of the covalent organic material prepared in Example 1 of the present invention: (a) XRD; (b) IR; (c) BET; (d) pore size distribution.

[0034] Figure 3 It is a schematic diagram of the process of preparing the composite diaphragm in Example 2 of the present invention.

[0035] Figure 4 I3 prepared from the composite diaphragm in Example 2 of the present invention - Results of penetration test.

[0036] Figure 5 It is a symmetrical and semi-symmetrical battery cycle performance diagram of the composite membrane assembly prepared in Application Example 1 and Application Example 2 of the present invention.

[0037] Figure 6 This is the cycling performance diagram of the zinc-iodine full battery assembled with the covalent organic material composite membrane prepared in Application Example 3. DETAILED DESCRIPTION

[0038] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0039] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0040] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0041] Example 1

[0042] Preparation of two-dimensional covalent organic framework materials:

[0043] 1,3,5-tri(p-formylphenyl)benzene (26 mg) and oxalylhydrazide amide (15 mg) were added to a reaction tube, ultrasonically dispersed with o-dichlorobenzene and n-butanol (0.5 mL each), and acetic acid solution (6M, 0.2 mL) was added, frozen with liquid nitrogen for 5 minutes, flame sealed, and heated at 120°C for 3 days. After cooling to room temperature, a solid powder was obtained, which was washed with anhydrous tetrahydrofuran (THF) and vacuum dried at 120°C to obtain a khaki covalent organic framework material.

[0044] Example 2

[0045] Preparation of two-dimensional organic framework material composite membrane:

[0046] 10 mg of the two-dimensional covalent organic framework material prepared in Example 1 was dispersed in 50 mL of anhydrous ethanol solution, 2 mL of 5% polyvinylidene fluoride was added, and then 5 mg of graphene was weighed and dispersed in 50 mL of anhydrous ethanol, and 2 mL of 5% polyvinylidene fluoride was added. The mixture was filtered sequentially on a 40 mm circular diaphragm by suction.

[0047] Example 3

[0048] Preparation of two-dimensional organic framework materials:

[0049] 1,3,5-tri(p-formylphenyl)benzene (26 mg) and oxalylhydrazide amide (15 mg) were added to a reaction tube, ultrasonically dispersed with o-dichlorobenzene and n-butanol (0.5 mL each), and acetic acid solution (12M, 0.2 mL) was added. The mixture was frozen with liquid nitrogen for 5 minutes, flame sealed, and heated at 120°C for 3 days. After cooling to room temperature, a solid powder was obtained, which was washed with anhydrous THF and vacuum dried at 120°C to obtain a khaki covalent organic framework material.

[0050] Example 4

[0051] Preparation of two-dimensional organic framework material (TFPA-HAD-COF):

[0052] Step 1, tri(4-formylphenyl)amine (20 mg) and oxalylhydrazide amide (15 mg) were added to a reaction tube, ultrasonically dispersed with o-dichlorobenzene (0.3 mL) and n-butanol (0.7 mL), acetic acid solution (6 M, 0.3 mL) was added, liquid nitrogen was frozen for 5 minutes, flame sealed, and heated at 120° C. for 3 days. After cooling to room temperature, the solid powder was washed with THF and vacuum dried at 120° C. to obtain a khaki covalent organic framework material (TFPA-HAD-COF).

[0053] Example 5

[0054] Preparation of two-dimensional organic framework material (TATB-HAD-COF):

[0055] Step 1, add 30 mg of 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine and oxalylhydrazide amide (15 mg) to a reaction tube, ultrasonically disperse with o-dichlorobenzene (0.6 mL) and n-butanol (0.4 mL each), add acetic acid solution (6M, 0.1 mL), freeze with liquid nitrogen for 5 minutes, flame seal, and heat at 120°C for 3 days. After cooling to room temperature, a solid powder is obtained, extracted with THF for 24 hours, and vacuum dried at 120°C to obtain a light yellow covalent organic framework material (TATB-HAD-COF).

[0056] Application Example 1

[0057] Preparation of the battery:

[0058] The composite diaphragm obtained in Example 2 was cut into discs with a diameter of 1.8 cm, and then a zinc sheet with a diameter of 9 mm was used as the negative electrode, and a zinc salt aqueous solution was used as the electrolyte to assemble a button battery, including a negative electrode, a spring, a gasket, a composite diaphragm, an electrolyte and a zinc foil (a semi-weighed battery is a 12 mm copper foil), and a negative electrode shell.

[0059] Semi-balanced battery preparation method: The assembly of button-type semi-balanced battery is carried out under normal conditions. The battery shell model is CR2032, the positive and negative electrodes are made of metal zinc sheets, and the positive electrode is made of metal copper sheets. The positive and negative electrodes are separated by a composite diaphragm, in which the side with the modified coating faces the copper positive electrode. The injection volume of the electrolyte is 100μL. The electrolyte is composed of 2M zinc sulfate solution. After adding the electrolyte, the button-type semi-balanced battery is assembled.

[0060] Application Example 2

[0061] Preparation of the battery:

[0062] The composite diaphragm obtained in Example 2 was cut into discs with a diameter of 1.8 cm, and then a zinc sheet with a diameter of 9 mm was used as the negative electrode, and a zinc salt aqueous solution was used as the electrolyte to assemble a button battery, including a negative electrode, a spring, a gasket, a composite diaphragm, an electrolyte and a zinc foil (a semi-weighed battery is a 12 mm copper foil), and a negative electrode shell.

[0063] Symmetrical battery preparation method: The assembly of button-type semi-symmetrical batteries is carried out under normal conditions. The battery shell model is CR2032, both electrodes are made of metal zinc sheets, and the two electrodes are separated by a composite diaphragm. The injection amount of electrolyte is 100μL. The electrolyte is composed of 2M zinc sulfate solution. After adding the electrolyte, the button-type symmetrical battery is assembled.

[0064] Application Example 3

[0065] Preparation of the battery:

[0066] The composite diaphragm obtained in Example 2 was cut into discs with a diameter of 1.8 cm, and then a zinc sheet with a diameter of 9 mm was used as the negative electrode, and a zinc salt aqueous solution was used as the electrolyte to assemble a button battery, including a negative electrode, a spring, a gasket, a composite diaphragm, an electrolyte and a zinc foil (a semi-weighed battery is a 12 mm copper foil), and a negative electrode shell.

[0067] Preparation method of full battery: The assembly of button-type full battery is carried out under normal conditions. The model of the battery shell is CR2032, the negative electrode uses a metal zinc sheet, and the positive electrode uses an iodine-absorbing activated carbon electrode. The positive and negative electrodes are separated by a composite diaphragm, in which the side with the modified coating faces the iodine-absorbing activated carbon positive electrode. The injection volume of the electrolyte is 100μL. The electrolyte is composed of 3M zinc sulfate solution and 0.4 and zinc iodide solution. After adding the electrolyte, the button-type full battery is assembled.

[0068] See also Figure 1 , a yellowish covalent organic framework material was obtained. Further characterization of its XRD, IR, and BET results showed that Figure 2 shown. Figure 3 A schematic diagram of the general process of preparing the two-dimensional organic framework material composite membrane of Example 2 and its optical photograph are shown.

[0069] See also Figure 4 , I3 of the composite diaphragm prepared in Example 2 of the present invention - The results of the penetration test, in which a common glass fiber diaphragm was used in the electrolytic cell to test I3 - The left side is 1MZnSO4+0.1MZnI2 ​​aqueous solution, and the right side is 1MZnSO4 aqueous solution. The middle is a common glass fiber diaphragm. After standing for 4 hours, it was found that the right side turned light yellow after 4 hours. The solutions on both sides of the composite diaphragm of the present invention did not change color, proving that the ordinary diaphragm can pass I3 - , composite diaphragm for I3 - Has a good inhibitory effect.

[0070] The battery performance of the corresponding use case 1 and application case 2 is tested. Figure 5 It can be seen that the battery is at 10mA·cm -2 Even with the high current density, it can still cycle for 150 hours.

[0071] The full battery cycle performance test is carried out according to case 3. Figure 6 It can be seen that the full battery has 6.0 mAh cm -2 The initial high surface capacity at a current density of 20 mA cm -2 , it can still stably cycle for a long time of 550 cycles (1110 hours).

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A two-dimensional organic framework material, characterized in that: The structure of the two-dimensional organic framework material is as follows (1):

2. A method for synthesizing a two-dimensional organic framework material according to claim 1, characterized in that: The synthesis method comprises the following steps: (1) Mixing monomer A and ligand B, adding an organic solvent for ultrasonic dispersion, adding a catalyst after dispersion, freezing in liquid nitrogen for 5-10 minutes, sealing after freezing, and heating at 80-150° C. for reaction for 60-90 hours to obtain a mixed solution; (2) washing the mixed solution and drying at 110-130° C. to obtain a finished product; The monomer A includes one of 1,3,5-tri(p-formylphenyl)benzene, tri(4-formylphenyl)amine, tetraaminophenylmethane or triazine ring; The ligand B includes oxalylhydrazide amide or oxalyldiamide.

3. The method for synthesizing a two-dimensional organic framework material according to claim 2, characterized in that: In step (1), the mass ratio of the monomer A to the ligand B is 1-2:

1.

4. The method for synthesizing a two-dimensional organic framework material according to claim 2, characterized in that: In step (1), the organic solvent comprises o-dichlorobenzene and n-butanol in a mass ratio of 0.5-1:1, and the volume mass ratio of the organic solvent to the ligand B is 1 mL: 10-20 mg; The catalyst is an acetic acid solution, the volume ratio of the catalyst to the organic solvent is 1:5-7, and the concentration of the acetic acid solution is 6-12M.

5. Use of the two-dimensional organic framework material described in claim 1 in the preparation of zinc-iodine battery separators.

6. The method for preparing the zinc-iodine battery separator according to claim 5, characterized in that: The following steps are involved: (1) dispersing the two-dimensional organic framework material according to claim 1 in anhydrous ethanol, adding a binder A, and obtaining a mixed slurry A; (2) dispersing the conductive material in anhydrous ethanol and adding a binder B to obtain a mixed slurry B; (3) sequentially filtering the mixed slurry A and the mixed slurry B on the base film, and drying them to obtain a zinc-iodine battery separator; 7. The method for preparing a zinc-iodine battery separator according to claim 6, characterized in that, in step (1), the mass percentage of the binder in the binder is 1-10%; The mass ratio of the two-dimensional organic framework material to the binder A is 1-7:1, and the mass ratio of the conductive material to the binder B is 8-10:1; The conductive material is one of ketjen black, graphene and graphyne.

8. The method for preparing a zinc-iodine battery separator according to claim 6, characterized in that: In step (1), the binder A and the binder B are one or more of waterborne polyurethane, polyvinylidene ether carbonate, and polyvinylidene fluoride; The polymer molecular weight of the polyvinylidene fluoride is 1-100,000. When the polyvinylidene fluoride is used as a binder, N-methylpyrrolidone is used to prepare a polyvinylidene fluoride solution with a mass concentration of 5% to 10%.

9. The zinc-iodine battery separator prepared by the preparation method according to any one of claims 6 to 8.

10. Use of the zinc-iodine battery separator according to claim 9 in the preparation of zinc-iodine batteries.

Citation Information

Patent Citations

  • Zinc-iodine battery diaphragm based on covalent organic framework as well as preparation method and application of zinc-iodine battery diaphragm

    CN115693022A

  • Preparation method and application of covalent organic framework self-supporting diaphragm

    CN117878528A

  • Zinc-iodine battery diaphragm, preparation method thereof and zinc-iodine battery

    CN118099663A

  • Zinc-iodine battery diaphragm, preparation method and application

    CN118263622A

  • High efficiency zinc-iodine adsorption-aided flow battery with a low cost membrane

    US20220085401A1

Cited By

  • COFs (covalent organic frameworks) waterborne polyurethane composite material as well as preparation method and application thereof

    CN121851689A